Engaging communication in conflict systemic practice - Littlejohn, Stephen W. (Thousand Oaks SAGE Publications, 2001)
Written from the authors' experience in conflict intervention in their private consulting practice, Engaging Communication in Conflict uses a communication perspective to address insights and methods in private mediation, small group facilitation, system design, large-scale interventions, and public-issue management. This book offers encouragement for a world sometimes overwhelmed by conflict and presents an expanded and pragmatic definition of peace.
Includes bibliographical references
Keywords: Conflict management